Conference on Nonlinear Optics and Novel Materials - Trippenbach, Marek; Van, Cao Long (Photonics Letters of Poland, 2016)
<!–[if gte mso 9]> Normal 0 21 false false false PL X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><span style="font-size: 8.0pt; font-family: "(Użyj czcionki tekstu azjatycki","serif"; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The current issue of the Photonics Letters of Poland contains 6 selected paper presented during the International Conference on Nonlinear Optics and Novel Materials held in Vinh in Vietnam. The conference was organized jointly by Vihn University and the Faculty of Physics, University of Warsaw.<!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>